Kajian Agregat di Kalimantan Tengah (Studi Kasus: DAS Barito) - Aldy Adiarto; Desi Riani; Desriantomy (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This research aims to determine the physical properties of aggregates available in the Barito Watershed (DAS), Central Kalimantan Province. The aggregates collected from each location are East Barito Regency, crushed stone aggregate, South Barito, sand aggregate, North Barito, crushed stone and sand aggregate, and Murung Raya, crushed stone and sand aggregate. Each aggregate sample is then tested in the laboratory to obtain specific gravity and absorption values, water, abrasion value for coarse aggregate and sand equivalent value for fine aggregate. The existence of aggregate quarries spread over six locations in the four districts of Barito watershed, there are sufficient deposit reserves for the next few years for regional development in Central Kalimantan, and based on the results of testing physical properties in the form of testing specific gravity, The best aggregate test results are stone aggregate from Puruk Cahu, Murung Raya Regency with an abrasion value of 17.044% and sand aggregate from Jelapat Subdistrict, South Barito Regency with a sand equivalent value of 78.94%.